Effects of the Measures Undertaken by the European Mediator Regarding the Protection of Human Rights - IGNAT, Claudiu (Journal of Advanced Research in Law and Economics; Vol 10 No 2 (2019): JARLE Vol X Issue 2(40) Spring 2019, 2020)
The research performs an accurate radiography regarding the measures the European Mediator unfolds in the Human Rights protection but also with regard to the social impact upon the European citizen. The European Mediator is a complement to the ombudsmen existing in each State. However, its competence is limited only to the European Union authorities, as it does not involve the ones of the Member States. Any possible reports between the European Mediator and the equivalent institutions from the European Union Member State can only be mutually supported as long as every ombudsman aims the fulfilment of the same main function, namely that of administration control and citizen protection.